A journall kept by John Jourdain in a voyage for the East Indies : Began att the Downes neer t' Sandwich the 23th of March, anno 1607 ... Untill anno 1617 - Jourdain, John (Adam Matthew Digital, 1607)
Ms. journal of John Jourdain's travels in Arabia and the territories of the Great Mughal